Omitting cardiophrenic lymph nodes in the treatment of patients with Hodgkin lymphoma via modified involved-site radiation therapy. Issue 11 (2nd November 2018) - Pinnix, Chelsea C.; Wirth, Andrew; Milgrom, Sarah A.; Andraos, Therese Y.; Aristophanous, Michalis; Pham, Mary; Hancock, Donald; Ludmir, Ethan B.; Gunther, Jillian R.; Fanale, Michelle A.; Oki, Yasuhiro; Nastoupil, Loretta; et al.
Abstract: Cardiophrenic lymph nodes (CPLNs) are occasionally involved in Hodgkin lymphoma (HL). We characterized the incidence of CPLN involvement among 169 HL patients and evaluated outcomes after treatment with omission of the CPLN region from the involved-site radiation therapy (ISRT) field. Three types of RT fields were used: standard (S)-ISRT, reduced-dose (RD)-ISRT (lower dose to CPLNs, standard to other sites), or modified (M)-ISRT (omission of CPLNs). CPLNs were involved at diagnosis in 29 patients (17%). Of the 20 patients who received RT after complete response to chemotherapy, 4(20%) received S-ISRT, 8(40%) RD-ISRT, and 8(40%) M-ISRT. The four-year progression-free survival was 94.7%. One relapse occurred at a non-CPLN site after RD-ISRT. The mean heart dose and volume of the heart that received 25 Gy was higher for S-ISRT patients compared to M-ISRT ( p = .043 and p = .025, respectively). Re-planning the M-ISRT cases as S-ISRT resulted in significant increase in cardiac doses.